Decompressing posthaemorrhagic ventricular dilatation significantly improves regional cerebral oxygen saturation in preterm infants. (19th February 2015) - Norooz, F; Urlesberger, B; Giordano, V; Klebermasz‐Schrehof, K; Weninger, M; Berger, A; Olischar, M
Abstract Aim This study aimed to delineate the impact of posthaemorrhagic ventricular dilatation (PHVD) on regional cerebral oxygen saturation (rcSO2) in preterm infants before and after ventricular decompression using near‐infrared spectroscopy (NIRS). Methods rcSO2 values were recorded, fractional tissue oxygen extraction (FTOE) was calculated, cerebral ultrasound scans were performed, and resistive indices and ventricular width were collected before and after decompression. Where possible, amplitude‐integrated electroencephalography (aEEG) and visual evoked potentials (VEPs) were recorded before and after decompression. Results We included nine preterm infants: nine with cranial ultrasound scan data, eight with NIRS data, seven with aEEG data and four with VEPs. The resistive index was stable and remained unchanged after decompression in all patients. Before decompression, the mean rcSO2 value was 42.6 ± 12.9% and increased to 55 ± 12.2% after decompression. With increasing ventricular width, FTOE showed a mean value of 0.51 ± 0.05 and decreased to a mean of 0.39 ± 0.12 after decompression. Amplitude‐integrated electroencephalography showed a more continuous pattern, and VEPs showed delayed latencies in all patients before intervention, improving afterwards. Conclusion Near‐infrared spectroscopy may be of additional clinical value in progressive PHVD to determine the optimal time point for ventricular decompression.